2014
DOI: 10.1016/j.jiph.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Lost in a haystack: The importance of physical re-examination

Abstract: We report an unusual case of varicella zoster in a 19-year-old, who presented with persisting fever even after her lesions began forming scabs. Fever workup for secondary complications was negative. A re-examination revealed an axillary eschar. She recovered completely with doxycycline. This report suggests the importance of keeping in mind, epidemiological data of common diseases in the locality, as well as the significance of a thorough physical examination in patients with fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…She was investigated for other causes of fever including dengue infection in view of conjunctival suffusion. In varicella, a fever generally lasts for three to five days, however, our child had a fever for more than a week (4). The most common infectious causes of fever in varicella are super-added infections of the skin due to Streptococcus pyogenes and Staphylococcus aureus (4,5).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…She was investigated for other causes of fever including dengue infection in view of conjunctival suffusion. In varicella, a fever generally lasts for three to five days, however, our child had a fever for more than a week (4). The most common infectious causes of fever in varicella are super-added infections of the skin due to Streptococcus pyogenes and Staphylococcus aureus (4,5).…”
Section: Discussionmentioning
confidence: 70%
“…She was positive for NS antigen by ELISA and the diagnosis was consistent with the dengue hemorrhagic fever. In varicella, even though co-infections with bacterial complications, particularly skin superinfections, hand-foot-mouth disease, scrub typhus are reported, dengue co-infection was not reported in the literature (2,4,5,(9)(10)(11). Rebahi et al (5), reported purulent meningitis in a child with varicella.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria and dengue are very frequently seen in areas with heavy rainfall, where water stagnation favors mosquito breeding and the displacement of rodents from their natural habitat. Scrub typhus with a varicella infection is a rare co-infection, and only a few cases have been published in literature till now [ 6 , 7 ]. Fever in varicella infection generally lasts for three to five days.…”
Section: Discussionmentioning
confidence: 99%